2009
DOI: 10.1038/emboj.2009.238
|View full text |Cite
|
Sign up to set email alerts
|

Regulated activity of PP2A–B55δ is crucial for controlling entry into and exit from mitosis in Xenopus egg extracts

Abstract: Entry into mitosis depends on the activity of cyclin-dependent kinases (CDKs). Conversely, exit from mitosis occurs when mitotic cyclins are degraded, thereby extinguishing CDK activity. Exit from mitosis must also require mitotic phosphoproteins to revert to their interphase hypophosphorylated forms, but there is a controversy about which phosphatase(s) is/are responsible for dephosphorylating the CDK substrates. We find that PP2A associated with a B55d subunit is relatively specific for a model mitotic CDK s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
383
2
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(429 citation statements)
references
References 46 publications
(62 reference statements)
25
383
2
11
Order By: Relevance
“…Similarly, inactivation of the cyclin B-Cdc2 complex by cyclin B degradation was sufficient to trigger mitotic exit. However, recent data from our and other laboratories has demonstrated that PP2A is highly regulated during mitotic entry and exit (3,10,11). Therefore, the old cell-cycle model now must be updated to include a different regulator of mitosis that modulates PP2A during this phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, inactivation of the cyclin B-Cdc2 complex by cyclin B degradation was sufficient to trigger mitotic exit. However, recent data from our and other laboratories has demonstrated that PP2A is highly regulated during mitotic entry and exit (3,10,11). Therefore, the old cell-cycle model now must be updated to include a different regulator of mitosis that modulates PP2A during this phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that the inhibition of PP2A phosphastase activity is required to allow the phosphorylation of cyclin B-Cdc2 substrates, which promotes entry and maintains mitosis (3,10,11). Therefore, we next analyzed the capacity of these cells to phosphorylate the different cyclin B-Cdc2 substrates at the different doses of siRNA (Fig.…”
Section: Mast-l Is the Functional Human Homolog Of Xenopus Greatwallmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Furthermore, PP2A silencing has been shown to upregulate downstream Cdk1 transcriptional targets and promote mitosis. 27,28 As such, the Greatwall-PP2A network has been proposed as a key signaling axis that promotes normal Cdk1-driven entry through mitosis. 29 PP2A also acts on other mitotic mediators, including the key mitosis-specific kinase, Polo-like kinase 1 (PLK1), which localizes to centrosomes during mitosis and when inactivated by PP2A is an important hallmark of G2/M arrest and activation of the DNA damage response.…”
Section: Inhibition Of Wnt/beta-catenin Signalingmentioning
confidence: 99%
“…It was a biochemical study using Xenopus extracts that underlined the importance of controlling phosphatases for mitotic entry. Mochida et al showed that activating cyclin BCdk kinase was not sufficient to drive cells into mitosis; a member of the PP2A phosphatase family that antagonized cyclin B-Cdk1 had to be inactivated too (Mochida et al 2009 Williams et al 2014). Phospho-ENSA is then slowly dephosphorylated by PP2A, which allows PP2A to reactivate once cyclin -Cdk and Greatwall kinase activity decline later in mitosis (Williams et al 2014).…”
Section: Inhibiting Protein Phosphatasesmentioning
confidence: 99%